Peningkatan Keaktifan, Kreativitas, dan Kompetensi Mahasiswa melalui Penerapan Model Pembelajaran Berbasis Life Skills - Irma Yulia Basri (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
In the recent years, the practice of Electricity and Electronics is oriented to lecturer based learning. The lecturer oriented learning can make learning process passive. In this context, the researcher tries to carry out an experiment of teaching concept, with bases on life skills. The purpose of the research is to describe the influence of application of teaching model on the basis of life Skills. The model can improve student activity, creativity and competency on Electricity and Electronics subject on July-December 2006 at Automotive Engineering FT UNP. The collected data analysis was analyzed by descriptive analysis. The research was found that teaching model improved student's activity, creativity and competency on Electric and Electronics subject.